Visible light‐active pure and lanthanum‐doped copper oxide nanostructures for photocatalytic degradation of methylene blue dye and hydrogen production - Muhammad Rafique; N. R. Khalid; Muneeb Irshad; Falak Shafiq; Muhammad Usman; Yasser Fouad; Muhammad Imran; Mohammad A. Assiri; Waqar Muhammad Ashraf (Energy Science & Engineering, 2023)
Abstract Clean water and renewable energy sources are becoming increasingly important in the current era, as well as a future challenge, and one of the potential solutions is photocatalysis. In the current study, a simple one‐step hydrothermal technique is employed to fabricate the pure and La‐doped CuO (0%, 1%, 3%, 5%, and 7%) photocatalysts. The influence of varying La concentration on structure, morphology, and optical properties is determined by scanning electron microscope (SEM), X‐ray diffraction (XRD), ultraviolet (UV)–visible spectroscopy, and photoluminescence. SEM showed that synthesized nanostructures are irregularly spherical and transform into needle‐like nanostructures on increasing La concentration. XRD revealed the monoclinic phase with a crystallite size of 15–23 nm. The UV–visible spectrum exhibited a decrease in the band gap of La‐doped CuO needle‐like nanostructures from UV to visible light. The composition and purity of synthesized nanostructures are evaluated via the energy‐dispersive X‐ray spectrum which revealed that needle‐like nanostructures are pure without any impurity traces. The synthesized nanostructures were used as a photocatalyst against methylene blue dye to examine their photocatalytic activity. The synthesized CuO‐3La photocatalyst exhibited excellent photocatalytic performance of dye degradation and hydrogen production 95.3 μmol h−1 g−1 with more than 97% cyclic stability. Therefore, the synthesized La‐doped CuO nanostructures are potential candidates for photocatalytic water splitting and hydrogen evolution.